Analysis Of Organizational Citizenship Behavior On Globalization Of Employee Cooperative Performance Of Small Micro Enterprises Cooperative Services In Fakfak District - Ferdinandus Odatus Desmon; Pompong B. Setiadi; Purwanto Purwanto; Roy Sumaryono (Jurnal Scientia, 2024)
Organizational implementation Citizenship behavior (OCB) in developing productive businesses through cooperatives should be able to be implemented throughout Indonesia. This is no exception for Fakfak district which is located in West Papua province, as one of the provinces on the easternmost side of the territory of the Unitary State of the Republic of Indonesia. The research aims to find strategies for analyzing organizations citizenship behavior (OCB) on the globalization of cooperative performance of employees of the micro and small enterprise cooperative service in Fakfak Regency. The research method is descriptive with a quantitative analysis approach . Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weighted value based on the assessment indicators obtained from the results of preliminary research. The research results are presented in the form of a spider web diagram which is equipped with an illustration of the shift share gap value , a root cause analysis diagram with weighting, and a regression equation model obtained from spss statistics toolkit version 2.3.